Método de avaliação da usabilidade para "serius games" com interação gestual para idosos - Simor, Fernando Winckler (2016)
population, surpassing the idea of entertainment and providing experiences in order to promote better conditions of physical and / or mental health. Considering this expansion, it is necessary to establish mechanisms in order to evaluate the usability of gesture-based interfaces. With this in mind, this project aims to propose a usability evaluation method for gesture-based serious games for older adults. In an effort to propose our method, an exploratory survey investigated different usability assessment approaches available in the literature. For instrument validation, we applied an experimental study with two versions of the Motion Rehab game. The subjects consisted of 10 older adults aged over 60 years, male and female volunteers of the Centro Regional de Estudos e Atividades para Terceira Idade , Passo Fundo, RS, Brazil. For data collection, we used a Socio Demographic Questionnaire, the Mini Mental State Examination, the Geriatric Depression Scale and the proposed assessment tool. The results indicated that the method allowed detecting that version 2.0 present better usability that version 1.0 of the game. These results indicate that the proposed method is valid to evaluate the usability of serious games designed for older adults